Managing the Culture of COVID-19 "New Normal" as a Motivation for University Students in South Africa - Bunmi I. Omodan; Cias T. Tsotetsi; Olugbenga A. Ige (Research in Social Sciences and Technology, 2021)
The advent of COVID-19 and its implication on university education has been the bone of contention in recent times. The COVID-19 emergency has led to a change in knowledge inputs, processes, and outputs. This trajectory has demotivated student approaches to their learning. In response to this revolution, this study provides motivational strategies through students' perspectives to respond to the underside of new normal among South African university students. Ubuntu underpins the study within the Transformative Paradigm lens and Participatory Research as a research design. Ten students of a particular module in a selected university in South Africa were chosen to participate in the study. They were selected using the snowballing sampling technique because the participants were under level 3 lockdown with little or no access to campus at the time of the study. Online interview via phone calls, email and WhatsApp, was conducted with the students, and the data were analysed using Thematic Analysis. The study revealed a lack of visualised physical engagement between students and their lecturers and unstable internet access and lack of the internet as the major challenges. The study, therefore, recommends solutions that there should be adequate provision of effective online audio-visual sessions with enough space for student-lecturer’s interactions and low-tech online sessions and content deliveries.